A comparison study on low-temperature properties of Stone Mastic Asphalts modified with PmBs or modified fibres. Issue 12 (14th October 2020) - Eskandarsefat, Shahin; Hofko, Bernhard; Sangiorgi, Cesare
ABSTRACT: A research was conducted to assess the effectiveness of different kinds of Modified Fibres (MF) on the thermal cracking performance of a Stone Mastic Asphalt (SMA) compared to the conventional SMA mixtures modified with SBS Polymer modified Bitumen (PmB). In addition, the capability of rubberised fibres to alleviate the thermal cracking sensitivity was investigated. Besides the main scope, a series of the same SMAs were also produced containing 25% of Reclaimed Asphalt Pavement (RAP) to investigate the effects of RAP on the low-temperature performance of the mixtures, which were modified either with MF or PmB. The experimental plan included both binder and mixture characterisation by means of Bending Beam Rheometer (BBR) test and Thermal Stress Restrained Specimen Test (TSRST). Binder-scale test results showed that the stiffness of all bituminous compounds is increased by the addition of fibres and rubber improves the elasticity of both neat and PmB compounds. In the mixture scale, TSRST results showed no significant difference between the mixtures. However it is noteworthy that, in addition, better low-temperature performance was recorded for virgin mixtures compared to to RAP containing ones. The overall results may confirm the feasibility of modified fibres in the modification of mixtures at low temperatures.